2016
DOI: 10.17645/si.v4i2.509
|View full text |Cite
|
Sign up to set email alerts
|

Religious Education in Russia: Inter-Faith Harmony or Neo-Imperial Toleration?

Abstract: This paper explores the approach to religious education that has been instituted in Russia since 2012. The new policy's manifestly proclaimed goals seem convergent with the values of religious freedom, self-determination, tolerance, and inter-faith peace that are espoused by Western liberal democracies. Yet Russia's hidden religious education curriculum is far more consistent with a neo-imperial model of ethno-religious (Russian Orthodox) hegemony and limited toleration of selected, other faiths whose reach is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…I agree with the authors who suggested that teaching religion is conducive to creating a very specific state ideology, which can be characterized as neotraditionalist, the main components of which are great-power ambitions, ethno-nationalism and Russian Orthodoxy (Willems, 2007;Lisovskaya, 2016Lisovskaya, , 2017. My study is a continuation of this research tradition.…”
Section: Objectivessupporting
confidence: 78%
See 2 more Smart Citations
“…I agree with the authors who suggested that teaching religion is conducive to creating a very specific state ideology, which can be characterized as neotraditionalist, the main components of which are great-power ambitions, ethno-nationalism and Russian Orthodoxy (Willems, 2007;Lisovskaya, 2016Lisovskaya, , 2017. My study is a continuation of this research tradition.…”
Section: Objectivessupporting
confidence: 78%
“…The ideology of teaching religion in the post-Soviet Russian public schools have been already examined by a number of researchers (Mitrokhin, 2000(Mitrokhin, , 2004(Mitrokhin, , 2005Glanzer, 2005;Halstead, 1994;Willems, 2007;Lisovskaya and Karpov, 2010;Shnirelman, 2011Shnirelman, , 2012Shnirelman, , 2017Köllner, 2016;Lisovskaya, 2016;Lisovskaya, 2017). It was shown that the introduction of religion-related courses is considered a visible embodiment of church-state relations, when the attempt to implement a model of church-state separation ultimately failed and "the regime increasingly drew upon the country's traditional religion not only as a source of legitimacy, but also for political support" (Marsh 2013: 20).…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence or absence of religious education classes as well as their content and who teaches them have been topics of contention in very diverse times and places for groups interested in influencing the dynamics of secularization (see, e.g., Jackson 1992 on the UK, Lisovskaya 2016 on the Russian Federation). Romania in the past decades has been no exception, especially as educational standards concerning professionalism, inclusion, and pluralism—such as those in OSCE's Toledo Guiding Principles on teaching about religion and beliefs 12 —have only gradually made their way into the curriculum.…”
Section: Religion In Romanian Public Education: a Historical Overviewmentioning
confidence: 99%